Petroleum’s Price Transmission and Imported Demand for Crude Oil in Thailand - Chaiwat, Papusson; Tangvitoontham, Nantarat (International Journal of Energy Economics and Policy, 2014)
The study of the petroleum price structures in Thailand reveals that diesel is the important fuel because it influences inflation and productions’ costs. Government wants to keep diesel’s price stability; meanwhile, it is less control in gasohol and petrol prices. These prices are normally higher than diesel’s price in order to support the renewable energy and reduce the consumption behaviors. Real price elasticity of imported crude oil in short run is insignificant but in long run is about 0.0660 statistically significant. While, real income elasticity is about 0.4841 in short run and increase to 0.9969 in long run. The price transmissions from crude oil to petroleum products demonstrate the inequality distribution with symmetry adjustments. Additionally, the adjustment to the long-run equilibrium of petrol price is slower than diesel price. Therefore, the efficiency energy policies should be in consideration to decrease the country’s energy consumption in the future. Keywords: price transmission; elasticity of crude oil demand JEL Classifications: C32; Q41; Q48